Measurement of Thermal Characteristics for IGBT Module and Thermal Characteristics Analysis of Its Inside Structure - ZHOU Wangjun; FENG Qin; WANG Xianyuan (Kongzhi Yu Xinxi Jishu)
Thermal characteristics of IGBT module structure are easily influenced by outside conditions, such as changes of packing technology or raw material performance. In this paper, structure function was used to obtain the junction thermal resistance inside module via practical calculation and test. Then thermal characteristics analysis was made for each layer inside IGBT module, in accordance with thermal resistance and thermal capacitance of different materials.